2010
DOI: 10.1208/s12249-010-9547-0
|View full text |Cite|
|
Sign up to set email alerts
|

Rheological Evaluation of Inter-grade and Inter-batch Variability of Sodium Alginate

Abstract: Abstract. Polymeric excipients are often the least well-characterized components of pharmaceutical formulations. The aim of this study was to facilitate the QbD approach to pharmaceutical manufacturing by evaluating the inter-grade and inter-batch variability of pharmaceutical-grade polymeric excipients. Sodium alginate, a widely used polymeric excipient, was selected for evaluation using appropriate rheological methods and test conditions. The materials used were six different grades of sodium alginate and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 35 publications
0
29
0
2
Order By: Relevance
“…[11–14] Quality by design (QbD) principle makes it necessary to establish a design space for each pharmaceutical product, active ingredient, excipient, and the unit operation used to produce the finished products and the excipients. [15–17] Polymer, as the name implies, is made up of repeating units and these repeating units can be of different lengths. The length of a polymer chain may be a key basis for some of its physicochemical properties and fractionation may affect these properties.…”
mentioning
confidence: 99%
“…[11–14] Quality by design (QbD) principle makes it necessary to establish a design space for each pharmaceutical product, active ingredient, excipient, and the unit operation used to produce the finished products and the excipients. [15–17] Polymer, as the name implies, is made up of repeating units and these repeating units can be of different lengths. The length of a polymer chain may be a key basis for some of its physicochemical properties and fractionation may affect these properties.…”
mentioning
confidence: 99%
“…Several researchers have now begun to incorporate QbD principles for the characterization of excipient variability. Fu et al determined the intergrade and interbatch variability of sodium alginate using appropriate rheological methods and conditions. This provided insight into the delineation of the design space as a part of QbD for sodium alginate‐based formulations …”
Section: Qbd and Excipient Variabilitymentioning
confidence: 99%
“…Moreover, quality by design (QbD) principles make it necessary to establish a design space for pharmaceutical products, active ingredients, excipients, and the unit operations used to produce the finished products and the excipients. [14][15][16] It has been suggested that rheology is the most sensitive method for material characterization because the flow behavior is responsive to properties such as molecular weight and molecular weight distribution. [17] Rheological measurements are also useful in following the course of a chemical reaction.…”
Section: Introductionmentioning
confidence: 99%